2016
DOI: 10.1007/s10905-016-9568-y
|View full text |Cite
|
Sign up to set email alerts
|

Lekking Behaviour and Male-Male Rivalry in the Melon Fly Bactrocera cucurbitae (Coquillett) (Diptera: Tephritidae)

Abstract: Most studies on the sexual behaviour of tephritid fruit flies are conducted in laboratory or field cage settings. Here, we present field data on the mating behaviour of the melon fly, Bactrocera cucurbitae (Coquillett). A number of Tephritidae are lekking species, forming aggregations in which males fight to defend a small territory where they court females and mate. Our results confirm that males of the melon flies congregated and engaged in wing vibration in the late afternoon on non-host plants, such as Fic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…Third, the mating advantage of large males may have reflected their dominance in aggressive encounters. Compared to some other tephritid species, and consistent with prior observations (Kuba & Koyama, ; Iwahashi & Majima, ; Mir & Mir, ), encounters between Z . cucurbitae males were not particularly elaborate or intense.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Third, the mating advantage of large males may have reflected their dominance in aggressive encounters. Compared to some other tephritid species, and consistent with prior observations (Kuba & Koyama, ; Iwahashi & Majima, ; Mir & Mir, ), encounters between Z . cucurbitae males were not particularly elaborate or intense.…”
Section: Discussionsupporting
confidence: 90%
“…Third, the mating advantage of large males may have reflected their dominance in aggressive encounters. Compared to some other tephritid species, and consistent with prior observations (Kuba & Koyama, 1985;Iwahashi & Majima, 1986;Mir & Mir, 2016), encounters between Z. cucurbitae males were not particularly elaborate or intense. In the olive fly Dacus oleae (Rossi), for example, aggressive interactions followed a regular sequence of behaviors, and males frequently pounced and head-butted one another in agonistic interactions lasting 15-20 s (Benelli, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Field observations in Japan showed that, despite the presence of a preferred host, males of the melon fly, Zeugodacus cucurbitae (Coquillett) (Diptera: Tephritidae), aggregated and displayed most frequently on nonhost (and herbaceous) species of Asteraceae ( Iwahashi and Majima 1986 ). Leks of this species were most commonly found on nonhost plants in India as well ( Mir and Mir 2016 ). In the wild tobacco fruit fly, Bactrocera cacuminata (Hering), a field-cage experiment indicated that nonhost plants containing the phenylpropanoid compound methyl eugenol, a known male attractant, serve as rendezvous sites for mating ( Raghu and Clarke 2003 ).…”
Section: Questions and Answersmentioning
confidence: 99%